The assumption of the virgin. Issue 3 (3rd July 2018) - Pettersson, Rune
Abstract: The Basilica di Santa Maria Gloriosa dei Frari in Venice is dedicated to the Assumption, the miraculous raising of Mary, mother of Jesus, into Heaven at the end of her earthly life. Five hundred years ago, 1518, the Italian Renaissance artist Titian finished his oil painting The Assumption of the Virgin. The purpose of this essay is to share my enthusiasm for this extraordinary painting and Titian's clear knowledge of visual communication. Titian used different perspectives, divine division, glowing colours, advanced light design and interesting visual compositions in order to communicate the religious drama when Mary was assumed into Heaven. These early insights are important for everyone interested in the foundations of visual communication and visual literacy.